Stepwise Luweero visual walk through - International Institute of Tropical Agriculture (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
This video walks the viewer through a Stepwise Luweero pilot site in a smallholder farmer field, capturing visual reference to each step of the Stepwise approach, highlighting conditions of the coffee in each step, and the incremental value of each set of practices applied by the farmer as part of the Stepwise approach being piloted.